(untitled) (Research, Society and Development, 2020)
Every field of science requires media that is relevant to its field. Teaching material that used is still general, until teaching materials that are specific to the field of science are needed to be effective in their use in learning. The aim of this research is to develop of mathematics learning media materials in faculty of teaching and education in Batanghari University Jambi, this research is using research and development approach (R&D) conducted at FKIP Batanghari University Jambi. The research subjects are 6th semester students 2017/2018. Development model that used is instructional development model (IDM). After the development has been done it needed validation by design expert, material expert, media expert. Then do one to one learner test, small group, and field trial. The result of the research based on validation by the expert is experts categorized as feasible with the percentage of eligibility for design validation 92.71%, media validation 89,78% and material expert 92,5%. It continue with one to one test with percentage 97,2%, small group 93%, and field trial 88,63%. The conclusion from validation result and the test that has been done so the mathematic Learning media materials is properly to used.